A network status evaluation method based on random projection - Jinming ZHAO (Dianxin kexue)
In recent years，machine learning has been widely used in network management.However，the complexity of the communication network is increasing，nonlinear and uncertain factors in the network make the machine learning more difficult.In order to improve the effect of machine learning，a scheme of artificial nervous network based on random projection was proposed.The characteristic of such scheme was the introduction of randomness in machine learning and network topology，which took the learning process more adaptability，and achieve faster and more accurate convergence.